2008
DOI: 10.1029/2008jd010315
|View full text |Cite
|
Sign up to set email alerts
|

A study of X‐ray emission from laboratory sparks in air at atmospheric pressure

Abstract: [1] We present a detailed investigation of X-ray emission from long laboratory sparks in air at atmospheric pressure. We studied 231 sparks of both polarities using a 1-MV Marx generator with gap lengths ranging from 10 to 140 cm. The X rays generated by the discharges were measured using five NaI/PMT detectors plus one plastic scintillator/PMT detector, all enclosed in 0.32-cm-thick aluminum boxes. X-ray emission was observed to accompany about 70% of negative polarity sparks and about 10% of positive polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 27 publications
7
101
0
1
Order By: Relevance
“…The latter study confirmed the production of X-rays from long laboratory sparks in air at atmospheric pressure obtained by Dwyer et al (2005a) as opposed to mmcm-long discharges mentioned above. Recently, another study (Dwyer et al, 2008) was conducted by combining the X-ray detector system used in Dwyer et al (2005b) study and the high voltage facilities used in the study of Rahman et al (2008). The results of this study too confirmed the results obtained previously by Dwyer et al (2005b) and Rahman et al (2008).…”
Section: Introductionsupporting
confidence: 93%
“…The latter study confirmed the production of X-rays from long laboratory sparks in air at atmospheric pressure obtained by Dwyer et al (2005a) as opposed to mmcm-long discharges mentioned above. Recently, another study (Dwyer et al, 2008) was conducted by combining the X-ray detector system used in Dwyer et al (2005b) study and the high voltage facilities used in the study of Rahman et al (2008). The results of this study too confirmed the results obtained previously by Dwyer et al (2005b) and Rahman et al (2008).…”
Section: Introductionsupporting
confidence: 93%
“…The two types of distributions considered produce similar results for the mean energy and for the total number of photons. Despite being slightly different from previous estimates reported in [7,[13][14][15][16], the values derived in this study are of the same order of magnitude as these previous estimates.…”
Section: Discussionsupporting
confidence: 44%
“…Several reports on the observation of x-rays with lightning impulse generators have been published [12][13][14]. Up to a few metre distance between detector and discharge is usually maintained because of safety.…”
Section: Resultsmentioning
confidence: 99%
“…X-rays can also occur during the initiation of sparks in the laboratory on a scale of millimetres up to metres, even with standard atmospheric conditions of approximately 1 bar and 20 • C. Unrolling adhesive tapes generates x-rays [9], as do helium-filled spark chambers [10], the formation of corona discharges [11] on a centimetre scale, or metre long discharges [12][13][14][15]. X-rays are a common feature of a high-voltage (HV) discharge, regardless of size.…”
Section: Introductionmentioning
confidence: 99%